HIV in pregnancy: a study of 30 cases in a tertiary care center in Mumbai, India - Kulkarni, Sejal; Palve, Tushar; Bulchandani, Priya; Devnikar, Komal; Thatikonda, Rajashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: HIV/AIDS infection is a significant cause of perinatal morbidity/mortality. Appropriate antiretroviral therapy should be given to all HIV-positive pregnant women to reduce the burden of the infection on mothers and children. The objective of this study was to evaluate the prevalence of HIV infection in pregnant women among age, parity, and mode of delivery and to observe the clinical features, co-existing infections, and various pregnancy outcomes in HIV-positive pregnant women. Methods: It is a type of research article. The present study was conducted in Unit 2, Department of Obstetrics and Gynaecology, Cama and Albless Hospital, Mumbai, Maharashtra, India, from a period of January 2022 to July 2022, 30 HIV-positive ANC mothers were examined. Results: About 30 ANC mothers participated in the study in which most of the subjects belonged to the 23-39 years of age group. Maximum patients are multipara. Conclusions: We found most (66.6%) of the ANC women with HIV-positive status delivered a healthy baby at term.